Pesan Moral Dalam Kisah Kesabaran Nabi Ayub as - Miftakul Mu’minin; Mugiyono Mugiyono; Muhammad Arpah Nurhayat (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2020)
The patience of the Prophet Job in the face of various trials, should be followed by other human beings. But there are some people who still take shortcuts far from what God almighty taught. In particular this paper departs from two problems, namely: how the Prophet Ayyub was patient in dealing with various trials and what moral message can be taken from the patience of the Prophet Ayyub. The type of research used is literature research using the primary data of the Quran and skunder data which includes various sources that have a connection to the discussion, then collect the data by reading, recording, grouping according to the nature and type, connecting between existing data and analyzing it. So it is concluded that in the face of various trials the Prophet Ayyub received it sincerely, did not complain and did not stay away from Allah Almighty.